Hubungan Pengetahuan Tentang Obesitas, Keragaman Konsumsi Makanan Sumber Karbohidrat dan Serat dengan Kejadian Obesitas Siswa SMA Kesatrian 2 Semarang - Azizah Nur Astiningrum; Agustin Syamsianah; Mufnaetty Mufnaetty (Universitas Muhammadiyah Semarang, 2017)
Obesity is a condition in which a person who is overweight due to accumulation of fat in the body. Obesity can increase the risk of chronic disease such as diabetes, high blood pressure, stroke, cancer, gout, etc. Obesity is associated with various factors, including genetic, psychological, diet, and physical activity. The purpose of this research is to know the relationship of knowledge about obesity, diversity of food consumption of carbohydrate source and fiber with obesity occurrence of SMA Kesatrian 2 Semarang student. The type of this research is analytic research using cross-sectional design. Thepopulation in this research is all students of SMA Kesatrian 2 Semarang which have 839 students. Samples taken as many as 55 people, sampling technique used is Systematic Random Sampling. Correlation between variable knowledge about obesity, diversity of food consumption of nutrition source with obesity incidence analyzed using Chi square test. The results showed that the average amount of food consumption diversity source of carbohydrate as much as 10.71 ± 1.04833 and the average amount of consumption as much as 13.07 ± 1.92310. The results found 22 students (40%) suffer from obesity. Chi Square statistic analysis showed no correlation between knowledge about obesity and obesity incidence (p = 0,727), there was no correlation between food consumption consumption of carbohydrate source and obesity incidence (p = 0,642), and there was no correlation between food consumption of fiber source and obesity incidence (P = 0.653). Conclusion: Knowledge about obesity, diversity of food consumption of carbohydrate source and diversity of food consumption of fiber source not related to obesity incidence in SMA Kesatrian 2 Semarang. Keywords: Knowledge about obesity, carbohydrate source, fiber, obesity incidence.